Was there a way out?: Nexus among domestic violence, stressors, and resources During COVID-19 among the urban middle-class families in Bangladesh (Social Science Review, 2024)
This article examines how different stressors created and aggravated by COVID-19 put urban middle-class families in a situation that leads to domestic violence, particularly in the unavailability of resources to deal with the stressors. A mixedmethod approach with an online questionnaire survey, in-depth interviews, and key informant interviews has been applied for a detailed understanding of the experiences of pandemic-induced stressors and the risk of domestic violence. Based on the Exosystem Factor Theory, the findings resonate that the pandemic created several stressors in urban middle-class families, including fear and anxiety, financial insecurity, gender role stress, disturbed interpersonal relationships, and disrupted support systems. This study further demonstrates that these stressors lead to domestic violence, where external and internal resources, such as alternative financial support, personal traits, women’s agency, rehabilitation support, and government and community support, do not appear to mediate the stressors.Social Science Review, Vol. 40(2), December 2023 Page 1-22